2019
DOI: 10.15252/embj.201899839
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated calcium signalling in cochlear sensory and non‐sensory cells refines afferent innervation of outer hair cells

Abstract: Outer hair cells (OHCs) are highly specialized sensory cells conferring the fine‐tuning and high sensitivity of the mammalian cochlea to acoustic stimuli. Here, by genetically manipulating spontaneous Ca2+ signalling in mice in vivo, through a period of early postnatal development, we find that the refinement of OHC afferent innervation is regulated by complementary spontaneous Ca2+ signals originating in OHCs and non‐sensory cells. OHCs fire spontaneous Ca2+ action potentials during a narrow period of neonata… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
104
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(113 citation statements)
references
References 80 publications
(147 reference statements)
6
104
0
Order By: Relevance
“…20 Therefore, it remains to be established if and how these two types of spontaneous activities correlate with each other. This stands out a key open question for cochlear physiopathology, as connexin expression and spontaneous Ca 2+ signaling in the GER are essential for normal development of the sensory epithelium, hair cell functional maturation, hearing acquisition, [20][21][22][23] redox homeostasis and age-related hearing loss. 24 We are confident that the technological advances presented here have the potential to shed light on this as well as a plethora of other unrelated open issues that concern the role of paracrine signaling in physiology and pathology 93 and cannot be addressed with standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…20 Therefore, it remains to be established if and how these two types of spontaneous activities correlate with each other. This stands out a key open question for cochlear physiopathology, as connexin expression and spontaneous Ca 2+ signaling in the GER are essential for normal development of the sensory epithelium, hair cell functional maturation, hearing acquisition, [20][21][22][23] redox homeostasis and age-related hearing loss. 24 We are confident that the technological advances presented here have the potential to shed light on this as well as a plethora of other unrelated open issues that concern the role of paracrine signaling in physiology and pathology 93 and cannot be addressed with standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, outer hair cells were also shown to exhibit spontaneous calcium transients, which were stimulated by neighboring Deiters' cells. Pharmacological blockade of P2rx3 receptors inhibited the firing dynamics of outer hair cells, and this altered normal patterns of outer hair cell ribbon synapse distribution and innervation (Ceriani et al, 2019). Extracellular ATP is also known to excite Type II SGNs (Weisz et al, 2009), and recent studies have shown that purinergic signaling occurs in Type II SGNs in response to hair cell damage (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This sensory input-independent firing of IHCs is fundamental for the maturation, pruning, and maintenance of the hair cell—auditory neuron synapses [7,8,25,27]. A recent study demonstrated that this autocrine and paracrine purinergic signaling does not only drive the development of IHCs in the greater epithelial ridge (GER, Kölliker’s organ), but it is also crucial for OHC maturation in the lesser epithelial ridge (LER) [28]. Deiters’ cells, the supporting cells in the LER, are paramount players in this process.…”
Section: Introductionmentioning
confidence: 99%